Peran Self-Compassion terhadap Dimensi-dimensi Kualitas Hidup Kesehatan pada Remaja Panti Asuhan - Annisa Zahra Kawitri; Ratih Arruum Listiyandini; Rina Rahmatika (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2020)
The purpose of thi study is to examine whether self-compassion can predict the level of health-related quality of life (HRQoL) among adolescents who live in foster care. The study used quantitative method with cross-sectional design. The sample were 140 teenagers recruited using convenience sampling technique from several foster care in Bekasi and Jakarta. Self Compassion Scale (SCSC) and KIDSCREEN-27 instrument were used to measure the level of self-compassion and HRQoL. Regression test was found that the influence of self-compassion toward HRQoL is significant on the dimension of physical wellbeing, psychological wellbeing, parent relations and autonomy, and school environment. However, self-compassion did not have significant influence toward health-related quality of life on the dimension of social support and peers. The role of self-compassion toward HRQoL implied that adolescents living at foster care need to develop a compassionate attitude for theirself in order to achieve better HRQoL.